2018
DOI: 10.26740/jpfa.v8n1.p33-41
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Transport Distance with Frequency-Dependent Volume Magnetic Susceptibility in Surabaya River Sediments

Abstract: Volume magnetic susceptibility measurements have been widely used in numerous studies related to river sediment characterization. A study of the transport distance effect toward the frequency-dependent volume magnetic susceptibility is needed to identify the superparamagnetic grain behavior in river sediments. The purpose of this study is to identify the presence of superparamagnetic grains and to obtain the relation between transport distances and frequency-dependent volume magnetic susceptibility in river se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…The magnetic field value obtained is then mapped in the contour of the magnetic field anomaly. Magnetic anomalies provide an overview of the non-uniformity of the Earth's magnetic field (Khalil & Santos, 2014;Mariyanto et al, 2018). This non-uniformity is caused by the distribution of magnetic objects that have different properties and characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…The magnetic field value obtained is then mapped in the contour of the magnetic field anomaly. Magnetic anomalies provide an overview of the non-uniformity of the Earth's magnetic field (Khalil & Santos, 2014;Mariyanto et al, 2018). This non-uniformity is caused by the distribution of magnetic objects that have different properties and characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…Beberapa studi suseptibilitas magnetik bergantung frekuensi telah dilakukan oleh peneliti (Kirana et al, 2021) melaporkan bahwa sampel tanah lapisan atas perkotaan di Kota Bandung dominan mengandung butir SP dalam sampel (<10%) atau hampir tidak ada butir SP yang memiliki rentang χFD 0,38-4,52% dengan rata-rata 1,89%. Kajian χFD pada sampel sedimen Sungai Surabaya dilakukan oleh (Mariyanto et al, 2018) yang menyatakan bahwa χFD sampel sedimen sungai termasuk pada kategori rendah dan medium. Selain itu juga, χFD pada sampel tanah lapisan atas di berbagai wilayah Jalingo, Negara Bagian Taraba, Nigeria dilaporkan berdasarkan berbagai jenis aktivitas manusia sebagian besar memiliki campuran butir SP dan butir non-SP yang lebih kasar atau butir SP < 0,05μm.…”
Section: Iunclassified
“…Several other studies have shown that magnetic susceptibility measurement was not only conducted on sediments from rivers [3], [4] but also on sediments from coasts [5], [6] and lakes [7], [8] and other materials such as mineral deposit [9] and guano [10], [11]. Previous studies have shown that frequency-dependent magnetic susceptibility was used to determine superparamagnetic grain content in sediments [12], [13].…”
Section: Datamentioning
confidence: 99%